(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2026)
This article investigates the interactive dynamics of carbon dioxide (CO₂) emissions, economic development, energy use, and industrial production for South Africa between 1990 and 2022. By employing a hybrid approach of wavelet coherence tests and Autoregressive Distributed Lag (ARDL) modeling, the article captures long-term elasticities as well as localized time-frequency associations between the variables. The findings confirm that economic development, energy use, and industrial production are significant determinants of CO₂ emissions and highlight the environmental challenges of South Africa’s development path. Policy responses highlight the imperative of integrated energy-efficacy strategies, renewable energy deployment, and greening of industry for sustainable development. The article contributes new findings to the literature with nuanced interpretations of the temporal and spectral properties of emissions dynamics, and its findings are useful for informing policymakers on carbon-emissions control for emerging economies.